Pemikiran Ibnu Hajar Al-Asqalani dalam Ilmu Administrasi Negara - Wisber Wiryanto (Department of Public Administration, 2021)
Ibn Hajar Al-Asqalani (773-852 H) was a classical Islamic scholar and an author of the Fathul Baari book which explains the Sahih Bukhari book. His book contains themes that discuss among others law in the maintenance of power and government in the State which is thought to have a connection with public administration sciences. Therefore, research about Ibn Hajar Al-Asqalani's thoughts in the public administration sciences was conducted, with a problem formulation, how the concept of Ibn Hajar al-Asqalani's thoughts in public administration sciences? The purpose of this study is to analyze Ibn Hajar Al-Asqalani's thoughts in public administration sciences from Fathul Baari's books. Library research methods are used to study the Fathul Baari books as a source of data/subject of research; then as the focus/object of research is public administration sciences. The data collected were processed and analyzed using induction and deduction techniques. The research was conducted in the first semester of 2020. The results of the study found a concept from Ibn Hajar Al-Asqalani’s thoughts in public administration sciences, which includes categories: leadership; government officials; personnel in the organization; governance; administrative principles; salary, and reward & punishment which is relevant to public administration sciences which are sourced from the Qur’an, hadith, and Islamic legacy. Next, stakeholders and related academics need to use these findings for educational, research, and development purposes public administration sciences using non-Western perspectives.